Bioremediation of maleic anhydride - F.L., Ng, Chin; EPI, H.S.; Leong, PE, Alex K.. (Malaysian Journal of Science, 2004)
This study was conducted to remediate the soil contamination issue identified in a petrochemical plant. Bioremediation was selected as the remedial options based upon a comprehensive Remedial Investigation/Feasibility Study (RI/FS) conducted earlier. This paper will present the findings of the bench scale bioremediation of Maleic Anhydride and its associated products, i.e. Phthalic Anhydride, Maleic Acid, Fumaric Acid and Benzoic Acid. The kinetic constant (K) and half-life of Maleic Anhydride were identified as —6.658 and 0.1 days, respectively. The K value and the half life of Maleic Anhydride are consistent with the available literature sources. The project was later scaled up for field implementation successfully